International Mission For Prognosis And Analysis Of Clinical Trials Score For Predicting Outcome In Moderate To Severe Traumatic Brain Injury - Phuyal, Suman; Gurung, Ashim; Karki, Anjan Singh; Sah, Hemant Kumar; Pradhanang, Amit Bahadur; Sedhain, Gopal; Shilpakar, Sushil Krishna; Sharma, Mohan Raj (Nepal Journal of Neuroscience, 2025)
Background: Traumatic Brain Injury (TBI) is a medical and surgical disease of major importance globally. Prognostic models are useful for making decisions in the clinical practice. The aim of this study was to assess the accuracy of International Mission for Prognosis and Analysis of Clinical Trials in TBI(IMPACT) score in predicting outcome in moderate to severe TBI in 6 months. Methods: All patients admitted to Tribhuvan University Teaching Hospital (TUTH) with moderate to severe TBI from April 2019 to February 2020were included in the study. IMPACT scores (core/extended core/ lab) were recorded separately at admission.Outcome was measured with Glasgow Outcome Scale (GOS)at the time of discharge and in six months.Correlation between observed and predicted outcomes was evaluatedbyPearson’s correlation coefficient (r). Sensitivity and specificity were plotted in the receiver-operating characteristic (ROC)curve, and the area under the curve (AUC) was calculated to determine the discrimination ability of this prognostic model. Results: A total of 139 patients were enrolled in the study. Twenty-four (17.3%) patients died within 6 months of TBI, and 40 (28.8%) patients had an unfavorable outcome.Pearson correlation coefficient showed good correlation between observed and predicted outcomes.The ROC curve indicated that all 3 models could accurately discriminate between favorable and unfavorable outcomes, as well as between survival and mortality(unfavorable outcome AUC= 0.905, 0.940, 0.955; mortality AUC= 0.875, 0.914, 0.917 respectively) in our patient population. Conclusions: The IMPACT score is a good prognosticmodel to predict 6-month outcomesin moderate to severeTBI at admission in Nepalese patient population.